EDUKASI KESEHATAN MASYARAKAT DI POSYANDU BANJAR PURNAMA ASRI, DESA PEGUYANGAN KANGIN, DENPASAR - Premayani, Ni Wayan Wina; Suardana, Anak Agung Komang; Dewi, Ni Gst Ayu Kd Diah Ambara; Pratiwi, Ni Putu Eka; Purnamayanti, Ni Made Ayu; Juniantari, Ni Made Sri (UNHI Press, 2025)
Community health is a crucial aspect in improving quality of life, particularly in urban areas such as Denpasar with its dynamic social conditions. The health education activity at Posyandu Banjar Purnama Asri, Peguyangan Kangin Village, was conducted as an effort to empower the community by enhancing their knowledge, attitudes, and healthy living behaviors. The purpose of this activity was to raise public awareness regarding the importance of clean and healthy living behaviors (PHBS), balanced nutrition, and the prevention of communicable and non-communicable diseases. The methods included interactive counseling, live demonstrations, distribution of educational leaflets, and discussion sessions with posyandu cadres and residents. The results showed an 85% increase in participants’ understanding based on simple pre- and post-tests, along with high enthusiasm and a strong commitment to practice healthy lifestyles within families. Additionally, posyandu cadres improved their capacity to independently provide health education to the community. In conclusion, the community health education program at Posyandu Banjar Purnama Asri was effective in enhancing public awareness and knowledge of health issues while strengthening the role of posyandu as the frontline of community-based health services.